An Assessment of Water-Energy-Food Nexus for Environmental Sustainability: The Case of Developing Economics - Mirza, Faisal Mehmood; Qurat-ul-Ann, Abre-Rehmat; Rizvi, Syed Badar-ul-Husnain; Iqbal, Nosheen (Pakistan Journal of Humanities and Social Sciences, 2023)
This study examines the water-energy-food nexus for environmental sustainability using panel data of developing economies from 1995-2017. Food index has been constructed using principle component analysis (PCA). Two-step difference generalized method of moment has been employed to estimate four models for assessment of the nexus in 77 developing economies from 1995-2017. Results indicate that the water, energy and food are closely related to each other as one sector affects the productivity of the remaining two sectors. Energy use and food index have strong positive effects on water productivity in developing economies. The environmental degradation of developing economies analyzed through the environmental Kuznets curve hypothesis confirms the inverted U-shaped relationship between environmental pollution and economic growth for developing economies. Study suggests that an integrated policy is required for the management of energy, water and food resources to avoid the water scarcity and food insecurity in the developing world.